Comparative Effectiveness of Reperfusion Strategies in Patients with ST-Segment Elevation Myocardial Infarction: A Secondary Analysis of the Acute Coronary Syndrome Quality Improvement in Kerala (ACS QUIK) Trial - Haitham Khraishah (Global Heart, 2020)
Introduction: Substantial heterogeneity exists in reperfusion strategies for patients with ST-segment myocardial infarction (STEMI) in low- and middle-income countries (LMICs). We sought to compare outcomes associated with primary percutaneous coronary intervention (PPCI) and non-primary percutaneous coronary intervention (nPPCI) reperfusion strategies in patients with STEMI in Kerala, India. Methods: We performed a retrospective analysis of patients with STEMI (n = 8665) from the Acute Coronary Syndrome Quality Improvement in Kerala (ACS QUIK) randomized trial receiving either PPCI (n = 6623) or nPPCI (n = 2042). nPPCI included all PCI strategies implemented when PPCI was not available including all post-fibrinolysis PCI strategies and PCI without fibrinolysis. Clinical outcomes among patients undergoing PPCI and nPPCI were compared after propensity-score matching. The main outcomes were the rates of in-hospital and 30-day major adverse cardiovascular events (MACE), defined as the composite of death, reinfarction, stroke, and major bleeding. Results: In the propensity-score matched cohort (n = 1266 in each group), nPPCI had longer symptom onset to hospital arrival time (347.5 vs. 195.0 minutes, p < 0.001), door to balloon time (108 minutes vs. 75 minutes, p < 0.001), and were less likely to receive a coronary stent (89.4% vs. 95%, p < 0.001), including drug-eluting stents (89.5% vs. 94.4%, p < 0.001). There were no clinically meaningful differences in discharge medical therapy. However, patients treated with nPPCI were less commonly referred for cardiac rehabilitation (20.2% vs. 24.2%; p = 0.019). In-hospital (3.6% vs. 3.3%, p = 0.74%) and 30-day (4.4% vs. 4.6%, p = 0.77) MACE did not differ between nPPCI and PPCI matched groups. Conclusion: In a large, contemporary population of STEMI patients from a LMIC, patients treated with a nPPCI reperfusion strategy had comparable short- and intermediate-term outcomes compared to PPCI despite differences in hospital presentation time and coronary stent use. These findings are reassuring but highlight the need for continued quality improvement in the delivery of STEMI care in resource-limited settings.